"Państwo celów" jako instytucja kultury. Czy krytyka władz podmiotu jest wystarczającą podstawą filozofii kultury? - Kozłowski, Marek (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2008)
Using E. Wolicka book "Consideration on Kant" as an anchoring point, the author investigates the conditions under which 'kingdom of ends' can successfully play a role of institution of culture, i.e. be translated into rules of action and empirical facts in the sphere of every day life and history.